Phosphorylation of myosin A regulates gliding motility and is essential for Plasmodium transmission - Ripp, Johanna; Smyrnakou, Xanthoula; Neuhoff, Marie-Theres; Hentzschel, Franziska; Frischknecht, Friedrich (EMBO reports, 2022)
Malaria-causing parasites rely on an actin-myosin-based motor for the invasion of different host cells and tissue traversal in mosquitoes and vertebrates. The unusual myosin A of Plasmodium spp. has a unique N-terminal extension, which is important for red blood cell invasion by P. falciparum merozoites in vitro and harbors a phosphorylation site at serine 19. Here, using the rodent-infecting P. berghei we show that phosphorylation of serine 19 increases ookinete but not sporozoite motility and is essential for efficient transmission of Plasmodium by mosquitoes as S19A mutants show defects in mosquito salivary gland entry. S19A along with E6R mutations slow ookinetes and salivary gland sporozoites in both 2D and 3D environments. In contrast to data from purified proteins, both E6R and S19D mutations lower force generation by sporozoites. Our data show that the phosphorylation cycle of S19 influences parasite migration and force generation and is critical for optimal migration of parasites during transmission from and to the mosquito.
Gesehen am 08.07.2022